Exosomes Derived from Hypoxia-Treated Human Adipose Mesenchymal Stem Cells Enhance Angiogenesis Through the PKA Signaling Pathway - Xue, Chunling; Shen, Yamei; Li, Xuechun; Li, Ba; Zhao, Sun; Gu, Junjie; Chen, Yunfei; Ma, Baitao; Wei, Junji; Han, Qin; Zhao, Robert C (Stem cells and development, 2018)
Angiogenesis is a complicated and sequential process that plays an important role in different physiological processes. Mesenchymal stem cells (MSCs), which are pluripotent stem cells, are widely used for the treatment of ischemic and traumatic diseases, and exosomes derived from these cells can also promote angiogenesis. Therefore, we aimed to uncover mechanisms to improve MSC exosome-mediated angiogenesis. For this study, we isolated human adipose-derived MSCs (hAD-MSCs) and assessed differentiation ability and markers. Cells were divided into hypoxia-treated MSCs (H-MSCs) and normoxia-treated MSCs (N-MSC), and exosomes were extracted by ultrafiltration. Exosomes (100 μg/mL) from H-MSCs and N-MSCs were added to human umbilical vein endothelial cells (HUVECs). Exosome uptake and the ability of endothelial cells to form tubes were detected in real time. Protein samples were collected at different time points to detect the expression of inhibitors (Vash1) and enhancers (Angpt1 and Flk1) of angiogenesis; we also assessed their related signaling pathways. We found that exosomes from the hypoxia group were more easily taken up by HUVECs; furthermore, their angiogenesis stimulatory activity was also significantly enhanced compared to that with exosomes from the normoxia group. HUVECs exposed to exosomes from H-MSCs significantly upregulated angiogenesis-stimulating genes and deregulated angiogenesis-inhibitory genes. The expression of vascular endothelial growth factor (VEGF) and activation of the protein kinase A (PKA) signaling pathway in HUVECs were significantly increased by hypoxia-exposed exosomes. Moreover, a PKA inhibitor was shown to significantly suppress angiogenesis. Finally, we concluded that hypoxia-exposed exosomes derived from hAD-MSCs can improve angiogenesis by activating the PKA signaling pathway and promoting the expression of VEGF. These results could be used to uncover safe and effective treatments for traumatic diseases.